An In-Situ Reference Electrode Insertion Method for Commercial 18650-Type Cells - Limhi Somerville; Stefania Ferrari; Michael J. Lain; Andrew McGordon; Paul Jennings; Rohit Bhagat (Batteries, 2018)
This work introduces a new method for inserting a Lithium reference electrode into commercially available 18650-type cells in order to obtain electrode potentials during cell operation. The proposed method is simple and requires limited equipment. Furthermore, electrical performance is significantly better and the cell capacity and resistance can be recorded for longer durations when compared to some of the previously used methods. Electrical performance of this new third electrode method is characterized and compared to 18650 cells with no reference electrode inserted. The capacity retention of the modified cell is more than 98% in the first 20 cycles. Harvested electrodes from a disassembled cell were also used to make coin cells that was proven to be a rather critical approach to get electrode potentials and capacities. This is an initial study that shows three-electrode performances of a commercial 18650-type cell, which suggests it could be used for understanding electrode behavior throughout a cell lifetime and for manufacturing instrumented cells.